Assessment of parasympathetic activity in athletes: comparing two dfifferent methods - Stang, J.; Couto, M.; Stensrud, T.; Mowinckel, P.; Moreira, A.; Carlsen, K.-H. (Medicine & Science in Sports & Exercise, 2016)
Introduction: A variety of methods are used to assess parasympathetic activity in athletes targeting different organs; however, the reliability of or interchangeability between measurement procedures is not clear.